2014
DOI: 10.1080/21683565.2014.953662
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Periurban Cattle Production Systems to Environmental Changes: Feeding Strategies of Herdsmen in Southern Benin

Abstract: We undertook a survey of 112 cattle farms in the periphery of Cotonou in Benin, with the aim to characterize the diversity of the production systems and to better understand herders' feeding strategies and perspectives. We used the Categorical Component Analysis and Two-step Clustering techniques to classify the farms into homogeneous groups. The adaptive strategy of a given farm was predicted through logistic regression analysis technique. Four distinct farm types were identified as follows: large integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…Studies have revealed that many farmers are aware of the adverse effects of climate variability [86,[88][89][90]. Farmers' observations have been established to be consistent with scientific assertions from empirical evidence [33].…”
Section: The Need For Csa In Sub-saharan African Agriculturementioning
confidence: 86%
“…Studies have revealed that many farmers are aware of the adverse effects of climate variability [86,[88][89][90]. Farmers' observations have been established to be consistent with scientific assertions from empirical evidence [33].…”
Section: The Need For Csa In Sub-saharan African Agriculturementioning
confidence: 86%
“…Small ruminants are essentially bred by smallholders and this activity generates an important household income during lean periods ( Babatoundé et al, 2010 ). In all Sub-Saharan African area, feed shortages remained the main constraint to ruminant breeding ( Adjolohoun et al, 2008 ; Koura et al, 2015 ). This is the result of agricultural pressure, urbanization and climate variability on the extensive production system, which now results in poor grazing areas ( Koura et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In all Sub-Saharan African area, feed shortages remained the main constraint to ruminant breeding ( Adjolohoun et al, 2008 ; Koura et al, 2015 ). This is the result of agricultural pressure, urbanization and climate variability on the extensive production system, which now results in poor grazing areas ( Koura et al, 2015 ). According to this author, in some areas of Southern-Benin, the most palatable species such as Panicum maximum and Pennisetum spp.…”
Section: Introductionmentioning
confidence: 99%
“…Declining soil fertility (Dercon, 2002;Vall et al, 2012), feed scarcity (Coulibaly, 2008;Vall et al, 2012;Koura et al, 2015) and reduction of space (Vall et al, 2006(Vall et al, , 2012Koura et al, 2015) threat the two productions (Dercon, 2002;Coulibaly, 2008;Koura et al, 2015) which can no more satisfy food availability. Integration of crop farming and livestock rearing is well known in West-Africa to improve the resilience of small farmers to ongoing risks Vall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%